Evaluating Housing Price Predictability of Alternative Hedonic Model Formulations - Liv Osland; Inge Thorsen (European Regional Science Association (ERSA), 2006)
We first use alternative hedonic model formulations to compare predicted and observed prices of property transactions in alternative locations. The estimation of model parameters is based on data from Western Norway, and the model formulations differ with respect to the representation of spatial structure. We discuss how measures like the distance to the cbd and a gravity based accessibility measure of labour market accessibility, contribute to predict spatial variations in housing prices. We also discuss how appropriate alternative models are to predict possible consequences on housing prices of changes in the spatial distribution of employment, and in the road transportation network. Finally, we recommend that a relative measure of labour market accessibility is introduced, to capture effects of spatial competition in the housing market.
Keywords: 330